KINERJA KARYAWAN DITINJAU DARI STRES KERJA, WORK ENGAGEMENT, PENEMPATAN DAN KEPEMIMPINAN (STUDI PADA FKIP UNS) - Esi Asmaryani; Bambang Mursito; Istiatin Istiatin (ITB AAS INDONESIA Surakarta, 2020)
The study aims to obtain empirical evidence the effect of work stress, work engagement, placement and leadership on employee performance at FKIP UNS. The type of research is survey research. The sample of this study used a purposive sampling sample. The data collection techniques was done using questionnaire. Data analysis was performed using multiple regression analysis. This study concludes that work stress, work engagement, placement and leadership affect the performance of FKIP UNS employees simultaneously and in part the work engagement does not affect employee performance. Keywords : Work Stress, work engagement, placement, leadership and employee performance